Board and Director Traits, Company Growth's Impact on Green Accounting Policy Moderated by Media Exposure - Dwiyani, Titik; Kristantiningtyas, Dhian; Apsari, Hirawresti Langen; Putra, Alfa Santoso Budiwidjojo (International Journal of Economics (IJEC), 2024)
This research aims to examine the gender characteristics, nationality, independence of the board of commissioners and directors in relation to green accounting policies with media exposure as a moderating variable. The population and sample of the study are mining companies listed on the Indonesia Stock Exchange (BEI) during the period 2020–2022. The usable population for the research, based on the required data, consists of 29 companies with observations over three years. The analysis method employed is panel data analysis using the EViews application. The research findings demonstrate that the variables of nationality characteristics and company growth have a significant positive influence. However, gender characteristics and the independence of commissioners and directors do not affect green accounting policies. The moderating variable, media exposure, only moderates the variables of nationality characteristics and company growth.